The Convergence of Corporate Governance Practices in Global Firms - Lindop, Charlotte (2012)
The matter of convergence in corporate governance practices has gained prominence in recent years as it becomes apparent that globalization in the capital markets has led to the expectation of transparency and accountability by investors, traits typically associated with firms based in the United Kingdom and United States. Whilst there is some argument for why there may be a persistence of diversity in corporate governance practices, there is more support for the view that there will be a convergence. Along with a number of others forces, including the failure of alternative systems, the status of Anglo-American firms as leaders in the global economy, and regulatory requirements, globalization, which as now moved into the realm of corporate governance, is pushing convergence to one globally accepted standard.